Seizures in Alzheimer disease: who, when, and how common? - Scarmeas, Nikolaos; Honig, Lawrence S; Choi, Hyunmi; Cantero, Julio; Brandt, Jason; Blacker, Deborah; Albert, Marilyn; Amatniek, Joan C; Marder, Karen; Bell, Karen; Hauser, W Allen; Stern, Yaakov (Arch Neurol, 2009)
BACKGROUND: Transient symptoms in Alzheimer disease (AD) are frequent and include seizures, syncope, and episodes of inattention or confusion. The incidence of seizures in AD and predictors of which patients with AD might be more predisposed to them is based primarily on retrospective studies and is not well established. OBJECTIVE: To determine the incidence and predictors of new-onset unprovoked seizures. DESIGN: Prospective cohort study. SETTING: Three academic centers. Patients Four hundred fifty-three patients with probable AD observed prospectively from mild disease stages since 1992. Main Outcome Measure Informant interviews every 6 months included questions about whether the patient had a seizure (convulsion, fainting, or "funny" spell) and whether diagnosis or treatment for epilepsy or seizure was made. Two epileptologists independently retrospectively reviewed all available medical records for 52 patients with positive responses to either of these questions, and using a specific checklist form, events were diagnosed as to whether they were unprovoked seizures (intrarater concordance, kappa = 0.67). Diagnosis of unprovoked seizures constituted the event in survival analyses. Potential predictors included sex, age, race/ethnicity, educational achievement, duration of illness, baseline cognition and function, depression, medical comorbidities, and time-dependent use of cholinesterase inhibitors and neuroleptic agents, apolipoprotein E genotype, and previous electroencephalographic findings. RESULTS: Over the course of 3518 visit-assessments (per patient: mean, 7.8; maximum, 27), 7 patients (1.5%) developed seizures. Younger age was associated with higher risk (hazard ratio, 1.23; 95% confidence interval, 1.08-1.41; P = .003 for each additional year of age) of seizure incidence. No other predictor was significant. The overall incidence of seizures was low (418 per 100 000 person-years of observation) although significantly higher than expected for idiopathic unprovoked seizures in similar age ranges of the general population (hazard ratio, 8.06; 95% confidence interval, 3.23-16.61). CONCLUSIONS: Unprovoked seizures are uncommon in AD, but they do occur more frequently than in the general population. Younger age is a risk factor for seizures in AD.
Keywords: Academic Medical Centers; Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Attention; Cohort Studies; Comorbidity; Confusion; Cross-Sectional Studies; Electroencephalography; Epilepsy; Female; Humans; Incidence; Kaplan-Meier Estimate; Male; Mental Status Schedule; Middle Aged; Prospective Studies; Risk Factors; Seizures; Syncope; United States